Laboratory set-up for education and research on automation of reverse osmosis plants employing a sustainable energy source - Badreddin, Essameddin; Gambier, Adrián; Aboul-Fotouh, Fuad (Desalination, 2004)
We report on preliminary experience of a laboratory-size reverse osmosis desalination plant employing a photovoltaic energy source. The plant is intended for educational and research purposes. The issues investigated are briefly discussed and preliminary operation measurement data are given. Further developments towards multiple energy sources, optimized plant configuration and potential applications are also mentioned. The plant was built in the framework of a cooperative project between the Automation Laboratory at the University of Mannheim (Germany), University of Applied Sciences (Zurich, Switzerland) and the Middle East Center of Energy and Environment Technology at the Arab Academy of Science and Technology (Alexandria, Egypt). The project was financially supported by the SwissContact Agency (Switzerland).